Analisis Tingkat Pemahaman dan Pengamalan Nilai Tasawuf pada Mahasiswa Tasawuf dan Psikoterapi UINSSC - Muhammad Wildan Al Maruf; Indri Wahyuni; Moja Yulia Paramita; Anggi Yus Susilowati (Indonesian Journal of Islamic Education, 2024)
The value of Sufism has an important role for each individual to achieve inner peace and closeness to God. In the context of modern education, such as in Sufism and Psychotherapy students, understanding and practicing the value of Sufism is often lacking or even not optimal. This study aims to analyze the level of understanding and practice of Sufism among students of Sufism and Psychotherapy, at the State Islamic University of Cyber Sheikh Nurjati Cirebon (UIN SSC). Through a quantitative method with a descriptive approach, this study collected data using a Bogardus scale questionnaire, which measured the understanding and practice of Sufism on 25 respondents. The results of this study indicate that the majority of Sufism and Psychotherapy students have a basic understanding of Sufism, and a low level of practice. Some of the factors that influence the low understanding and practice include the lack of pesantren education background, greater interest in psychotherapy, and challenges in applying the teachings of Sufism in everyday life. In addition, the majority of respondents felt that the teachings of Sufism did not have a significant impact on their lives. This research highlights the importance of increasing the understanding and practice of Sufism among Sufism and psychotherapy students, in order to optimize its positive impact in shaping character and inner peace, especially in the modern era.